The 3-dimensional printing for dental tissue regeneration: the state of the art and future challenges - Zhao, Fengxiao; Zhang, Zhijun; Guo, Weihua (Frontiers in Bioengineering and Biotechnology, 2024)
Tooth loss or damage poses great threaten to oral and general health. While contemporary clinical treatments have enabled tooth restoration to a certain extent, achieving functional tooth regeneration remains a challenging task due to the intricate and hierarchically organized architecture of teeth. The past few decades have seen a rapid development of three-dimensional (3D) printing technology, which has provided new breakthroughs in the field of tissue engineering and regenerative dentistry. This review outlined the bioactive materials and stem/progenitor cells used in dental regeneration, summarized recent advancements in the application of 3D printing technology for tooth and tooth-supporting tissue regeneration, including dental pulp, dentin, periodontal ligament, alveolar bone and so on. It also discussed current obstacles and potential future directions, aiming to inspire innovative ideas and encourage further development in regenerative medicine.